Ovarian function suppression: To what extent is it necessary for premenopausal patients with operable hormone-sensitive breast cancer? - P. V. Koposov (Опухоли женской репродуктивной системы, 2015)
The use of tamoxifen is conventional adjuvant hormone therapy in premenopausal patients with receptor-positive breast cancer. Clinical trials demonstrating the benefits of ovarian function suppression as adjuvant treatment had an ambiguous interpretation. There is no scientific evidence favoring the empiric use of ovarian suppression for these patients. The members of the American Society of Clinical Oncology consider that ovarian ablation or suppression should be used during adjuvant hormone therapy only in certain cases. Irreversible ovarian function ablation may improve time to relapse, by simultaneously deteriorating the quality of life in patients. Irreversible fertility loss in the patients who have experienced breast cancer may become a leading stressful factor for these patients. Many investigators believe that chemotherapy-induced amenorrhea reduces the risk of recurrence. The paper discusses the usage of gonadotropin-releasing hormone agonists in combination with tamoxifen and aromatase inhibitors during adjuvant hormone therapy for early breast cancer. Whether ovarian suppression is needed during hormone therapy is considered, it is the reversible ovarian function suppression that must be standard treatment in premenopausal patients.